XVII. Yüzyılda Bir Şair : Mehmed Sa'di Çelebi - Esir, Hasan Ali (İlim Yayma Cemiyeti, 2000)
This work is concerning the life and geography of Sa'di Çelebi as it appears in sources. This information which is gathered from the sources is enriched by the furthur informative elements derived from the poet's own works. The poet wrote his poems in the Arabic, Persian and Turkish languages. He is as much successful in prose as in poetry. He made translations as well. This work also includes exemplary poems by the author.
A Seventieth Century Poet : Mehmed Sa'di Çelebi
Keywords: Sa'di Çelebi; Divan Edebiyatı; Translation; Prose; Ottoman Science